2020
DOI: 10.1186/s13071-020-04115-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic studies on Strongyloides stercoralis in northern and western Thailand

Abstract: Background Strongyloidiasis is a soil borne helminthiasis, which in most cases is caused by Strongyloides stercoralis. Human infections with S. fuelleborni fuelleborni and S. fuelleborni kellyi also occur. Although up to 370 million people are currently estimated to be infected with S. stercoralis, this parasite is frequently overlooked. Strongyloides stercoralis is prevalent among humans in Thailand; however, S. fuelleborni fuelleborni has also been reported. Three recent genomic studies of individual S. ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
(105 reference statements)
4
18
0
Order By: Relevance
“…Our results from the pairwise F ST values found that sequences of worms isolated from migrants from Lao PDR, Cambodia and Myanmar were similar to those from Thailand, indicating close genetic relationship and high gene flow. This is consistent with a previous report, based on 18S rDNA and cox1 sequences, that S. stercoralis populations were not very differentiated between countries within the Southeast Asian peninsula [26]. Parasite gene flow is typically strongly influenced by host migration [29].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Our results from the pairwise F ST values found that sequences of worms isolated from migrants from Lao PDR, Cambodia and Myanmar were similar to those from Thailand, indicating close genetic relationship and high gene flow. This is consistent with a previous report, based on 18S rDNA and cox1 sequences, that S. stercoralis populations were not very differentiated between countries within the Southeast Asian peninsula [26]. Parasite gene flow is typically strongly influenced by host migration [29].…”
Section: Plos Onesupporting
confidence: 92%
“…Molecular identification of Strongyloides spp. is largely based on DNA sequences of mitochondrial (cytochrome C oxidase subunit 1 (cox1)) and nuclear ribosomal RNA regions (18S rDNA) [25,26]. Infection with S. stercoralis is more common than with S. fuelleborni and can have serious consequences, causing death in immunocompromised patients, those infected with human T-lymphotropic virus 1 (HTLV-1), organ-transplant patients, and those undergoing corticosteroid therapy [27].…”
Section: Introductionmentioning
confidence: 99%
“…While the two HVR-IV haplotypes and cox1 clades appeared to support genetically separate and isolated populations with differing host specificity, the HVR-I haplotype within these groups did not appear to correspond to these differing lineages (Jaleta et al, 2017;Nagayasu et al, 2017). Later work in northern Thailand identified two isolates from one patient which were almost identical by WGS but had distinct HVR-I haplotypes I and II, while another two worms from a different patient were very distinct on WGS but shared HVR-I haplotype II (Aupalee et al, 2020). In simple terms, while cox1 and HVR-IV sequences are viable markers of differing populations of S. stercoralis, HVR-I haplotypes do not appear to represent reproductively isolated populations and may not be applicable for this purpose (Aupalee et al, 2020).…”
Section: Strongyloides Stercoralis Is a Species Complex With Multiple...mentioning
confidence: 99%
“…Later work in northern Thailand identified two isolates from one patient which were almost identical by WGS but had distinct HVR-I haplotypes I and II, while another two worms from a different patient were very distinct on WGS but shared HVR-I haplotype II (Aupalee et al, 2020). In simple terms, while cox1 and HVR-IV sequences are viable markers of differing populations of S. stercoralis, HVR-I haplotypes do not appear to represent reproductively isolated populations and may not be applicable for this purpose (Aupalee et al, 2020).…”
Section: Strongyloides Stercoralis Is a Species Complex With Multiple...mentioning
confidence: 99%
See 1 more Smart Citation